Operational radiation safety program : recommendations of the National Council on Radiation Protection and Measurements. (NCRP report ;, 2022)
"This Report discusses the basic principles for establishing and maintaining an effective operational radiation safety program. It is intended for individuals with responsibility for these programs and assumes some level of formal education, training, and experience in radiation safety"--